2008
DOI: 10.1038/sj.onc.1211037
|View full text |Cite
|
Sign up to set email alerts
|

TERT promotes cellular and organismal survival independently of telomerase activity

Abstract: The expression level of the telomerase catalytic subunit (telomerase reverse transcriptase, TERT) positively correlates with cell survival after exposure to several lethal stresses. However, whether the protective role of TERT is independent of telomerase activity has not yet been clearly explored. Here, we genetically evaluated the protective roles of both TERT and telomerase activity against cell death induced by staurosporine (STS) and N-methyl-Daspartic acid (NMDA). First generation (G1) TERTdeficient mous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
107
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(112 citation statements)
references
References 48 publications
4
107
0
Order By: Relevance
“…TERT overexpression decreased apoptosis in PC12 cells induced by trophic factor withdrawal (Fu et al, 2000) and resulted in apparent resistance to cerebral ischemic injury and NMDA receptor-mediated neurotoxicity in the mouse brain . TERT downregulation increased the sensitivity of hippocampal neurons to excitotoxicity (Fu et al, 2000), and TERT-deficient neurons were more sensitive to NMDA than wild-type ones (Lee et al, 2008). Moreover, intrahippocampal AZT infusion caused 36.1% reduction in proliferation and 48.6% reduction in survival.…”
Section: Discussionmentioning
confidence: 98%
“…TERT overexpression decreased apoptosis in PC12 cells induced by trophic factor withdrawal (Fu et al, 2000) and resulted in apparent resistance to cerebral ischemic injury and NMDA receptor-mediated neurotoxicity in the mouse brain . TERT downregulation increased the sensitivity of hippocampal neurons to excitotoxicity (Fu et al, 2000), and TERT-deficient neurons were more sensitive to NMDA than wild-type ones (Lee et al, 2008). Moreover, intrahippocampal AZT infusion caused 36.1% reduction in proliferation and 48.6% reduction in survival.…”
Section: Discussionmentioning
confidence: 98%
“…In addition to increasing the canonical, telomere-maintenance function of hTERT, it is also possible that E6 increases hTERT protein to mediate noncanonical activities, such as apoptosis blockade (43)(44)(45), gene transcription (43,46,47), and cell proliferation (43,45,46), which could have important roles in the viral life cycle. It is very relevant that hTERT transcriptionally activates cellular gene sets that are very similar to those induced by the Wnt pathway (47) and might reflect its ability to convert primary keratinocytes into a stem-like state (mentioned above).…”
Section: Discussionmentioning
confidence: 99%
“…In this report, Lee et al have demonstrated by using both cell cultures and a transgenic mouse model that expression of TERT was directly associated with increased resistance to apoptosis induced by staurosporine (STS) or N-methyl-D-aspartic acid (NMDA) treatment. Importantly, these investigators have shown that the antiapoptotic effect of TERT was independent of telomere maintenance and telomerase activity [34].…”
Section: Telomerase In Apoptosismentioning
confidence: 99%
“…Recent studies showed that down-regulation of hTERT expression by hTERT specific interfering RNA (siRNA) sensitizes mitochondrial pathways of apoptosis without apparent involvement of telomere erosion due to telomerase inhibition, rather by post-translational activation of Bax protein which triggers a CD-90 independent mitochondrial pathway of apoptosis [33]. More recent report indicated that TERT promotes cellular and organismal survival independent of telomerase activity [34]. In this report, Lee et al have demonstrated by using both cell cultures and a transgenic mouse model that expression of TERT was directly associated with increased resistance to apoptosis induced by staurosporine (STS) or N-methyl-D-aspartic acid (NMDA) treatment.…”
Section: Telomerase In Apoptosismentioning
confidence: 99%